2019
DOI: 10.1080/25785826.2019.1660038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory B cell co-receptors and autoimmune diseases

Abstract: B cells express various inhibitory co-receptors including CD22 (also known as Siglec-2), Siglec-10 (Siglec-G in mice), CD72, LILRB (PIR-B in mice) and FccRIIB that contain immunoreceptor tyrosine-based inhibition motifs (ITIMs) in the cytoplasmic region and negatively regulate BCR signaling by recruiting phosphatases to the ITIMs. Some of the inhibitory B cell co-receptors suppress development of SLE. Among these, CD72 most strongly regulates SLE. CD72 recognizes Sm/RNP, a lupus self-antigen and an endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 73 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…The binding of sialic acid ligands to immune inhibitory siglecs results in immune evasion [40][41][42]. For example, blocking siglec-2 (CD22), an inhibitory B cell receptor specifically recognizing α2,6 sialic acids, increased tumor sensitivity towards immunotherapy [43][44][45]. Similarly, inhibiting siglec-7 and siglec-9 could protect tumor cells from NK cell responses [46].…”
Section: Sialic Acids Facilitate Immune Escapementioning
confidence: 99%
“…The binding of sialic acid ligands to immune inhibitory siglecs results in immune evasion [40][41][42]. For example, blocking siglec-2 (CD22), an inhibitory B cell receptor specifically recognizing α2,6 sialic acids, increased tumor sensitivity towards immunotherapy [43][44][45]. Similarly, inhibiting siglec-7 and siglec-9 could protect tumor cells from NK cell responses [46].…”
Section: Sialic Acids Facilitate Immune Escapementioning
confidence: 99%
“…It is expressed on human leucocytes, including B cells, eosinophils, monocytes, dendritic cells, T cells and NK cells [10][11][12][13][14]. Studies have shown that Siglec-10 plays an important role in regulating the immune balance of in ammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many autoimmune diseases could be regulated by various immune cells. For instance, CD22 and CD72 inhibited the proliferation of regulatory B cells, which can regulate MS and type 1 diabetes mellitus (T1D) ( Tsubata, 2019 ). Understanding the role of various immune cells in different autoimmune diseases can help enrich treatment options.…”
Section: Overview Of Autoimmune Diseasesmentioning
confidence: 99%